Substituição da farinha de peixes pelo concentrado proteico de soja para alevinos de tilápia do Nilo - Silva Neto, Manuel Rosa da (2017)
Different levels of substitution of fish meal (FP) by soy protein concentrate (CPS) on digestibility, performance and economic viability for Nile tilapia (Oreochromis nioloticus) fingerlings were evaluated. The apparent digestibility coefficients (CDA) of protein (CP) and dry matter (DM) CPS were evaluated with a diet composed of 69.5% of a reference diet, 30% of CPS and 0.5% of chromium oxide. CDA´s were 96.54 for PB and 75.62% for MS. Subsequently, two hundred and forty fingerlings with a mean initial weight of 5.10 ± 0.08g were distributed in a completely randomized design with five treatments and four replications, in 20 tanks of the 150L. The FP of the basal diet was gradually replaced by the PSC, giving the following levels: 0; 25; 50; 75 and 100%. These rations were formulated to contain 27.24% digestible protein and 3,031.00 Kcal ED.kg-1 feed. The water quality parameters are within the comfort range for the species. There were no significant differences (p> 0.05) for initial weight, survival, hepatosomatic index, viscerosomatic index and economic viability were not affected by the increasing levels of FP substitution by CPS. However, the final weight, weight gain, apparent feed intake, apparent feed conversion, specific growth rate, crude carcass protein, protein productive value, protein efficiency rate, were worsened with linear effect (p <0.05). Still in the morphometry, quadratic behavior was observed for goblet cells, increasing with the greater inclusion of CPS. It was concluded that the replacement of FP by CPS in diets for fingerlings is not recommended, as it has been shown to compromise performance, even though the economic efficiency was similar among the diets under study.